The Truth of the Hadith about the Reasons for the Revelation of Surah Al-KÄfirÅ«n and Its Effect on Religious Tolerance - Rohmansyah, Rohmansyah (Diroyah : Jurnal Studi Ilmu Hadis, 2022)
Hadithâ€™s authenticity on crucial things, such as tolerance in Surah Al-KÄfirÅ«n, must be studied. This paper aims to reveal and prove the status of the hadith as evidence of the revelation of Surah Al-KÄfirÅ«n, associated with religious tolerance. This study belongs to library research implementing a descriptive-analytic approach and a theoretical framework of the Sociology of Knowledge by Peter L Berger and Thomas Lukmann. The results unveiled that the hadith concerning the revelation of Surah Al-KÄfirÅ«n cannot be used as evidence because it was daif and mawquf. However, the tacitan of the hadith did not weaken the validity of the surah, of which the status is the word of God, which is qaá¹â€™Ä«. Therefore, Al-KÄfirÅ«nâ€™s correlation with religious tolerance remains valid as long as it pays attention to the determined limits. Mutual respect, assistance, and cooperation among religious people of different beliefs, and things unrelated to ideological aspects such as aqidah, worship, and sharia must be considered.The descent of suratÂ  al-KÄfirunÂ  exerts aÂ  considerable influence onÂ  the religiousness of the people. Every human being isÂ  freeÂ  to choose his religionÂ  according to his beliefsÂ  and their own beliefs. But especially MuslimsÂ  haveÂ  rulesÂ  thatÂ  stickÂ  to their religion, as well asÂ  non-Muslims. Mereka isÂ  freeÂ  to performÂ  worshipÂ  according to his understandingÂ  andÂ  belief. Surat al-KÄfirÅ«nÂ  in addition toÂ  teaching pluralityÂ  inÂ  religionÂ  alsoÂ  teaches the attitude of maintainingÂ  unityÂ  and unity ofÂ  the people,Â  reducingÂ  hostilityÂ  andÂ  eliminatingÂ  violenceÂ  and panaticÂ  againstÂ  other groups. The majesty ofÂ  suratÂ  al-KÄfirÅ«n became aÂ  wayÂ  out of the problemÂ  ofÂ  conflictÂ  betweenÂ  religiousÂ  peopleÂ  since its descentÂ  untilÂ  now so thatÂ  betweenÂ  religiousÂ  peopleÂ  live get along wellÂ  andÂ  don'tÂ  bother each other.Â